Functional properties of defatted chickpea flour heat-induced gels - Bi, Chonghao; Qie, Aoxue; Qie, Aoxue; Zhou, Tong; Zhou, Tong; Liu, Yi; Liu, Yi; Tian, Bin; Tian, Bin (International Journal of Agricultural and Biological Engineering, 2024)
Defatted chickpea flour (DCF), which is a by-product of chickpea oil extraction industry, is rich in nutrients that arebeneficial to human health. In this study, the effects of temperature and DCF variation on the rheological properties, waterholding capacity, freeze-thaw stability and microstructure of DCF heat induced gels were investigated. The results showed thatthe viscoelasticity, frequency dependence, and resistance strength of heat induced gels increased significantly with the increaseof temperature and DCF variation. The degree of denaturation and water retention of heat induced gels increased significantlywith increased variables within the temperature and variation windows of 75°C to 95°C and 13% to 21%. The CLSM resultsrevealed that variations of both temperature and DCF variation could cause the proteins in the heat induced gels to aggregategradually and to form protein aggregations. When temperature or variation exceeded certain value (85°C or 17%), the proteinaggregations broke up and the protein clusters became smaller and more homogeneous. Therefore, the heat induced gelspresented better water holding capacity, viscoelasticity, structural stability and gel property at a temperature of 95°C or a DCFvariation of 21% within the present experimental range.Keywords: defatted chickpea flour, rheological property, freeze-thaw stability, water holding capacity, microstructureDOI: 10.25165/j.ijabe.20241702.8035Citation: Bi C H, Qie A X, Zhou T, Liu Y, Tian B. Functional properties of defatted chickpea flour heat-induced gels. Int J Agric & Biol Eng, 2024; 17(2): 280–286.